2020
DOI: 10.1371/journal.pntd.0008076
|View full text |Cite
|
Sign up to set email alerts
|

Severe dengue categories as research endpoints—Results from a prospective observational study in hospitalised dengue patients

Abstract: Severe dengue was perceived as one clinical disease entity until the WHO 2009 classification stratified it into severe vascular leakage, severe bleeding, and severe organ dysfunction. The objectives of this study were to investigate the potential use of severe dengue categories as endpoints for intervention research. 271 patients with severe dengue among 1734 confirmed dengue patients were followed prospectively in this hospital-based observational study in Latin America and Asia. We compared the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
(36 reference statements)
0
21
0
Order By: Relevance
“…Severe plasma leakage often manifests as pleural effusion, ascites, hypoproteinemia, or hemoconcentration, causing NSD to progress to SD because of hypovolemic shock. 25 26 27 Our study observed that fluid accumulation was significantly associated with SD infection. If left untreated, patients with fluid accumulation will develop hypotension, followed by a rapid decline in systolic blood pressure, and irreversible shock and death may ensue despite resuscitation attempts.…”
Section: Discussionmentioning
confidence: 51%
“…Severe plasma leakage often manifests as pleural effusion, ascites, hypoproteinemia, or hemoconcentration, causing NSD to progress to SD because of hypovolemic shock. 25 26 27 Our study observed that fluid accumulation was significantly associated with SD infection. If left untreated, patients with fluid accumulation will develop hypotension, followed by a rapid decline in systolic blood pressure, and irreversible shock and death may ensue despite resuscitation attempts.…”
Section: Discussionmentioning
confidence: 51%
“…We acknowledge that only two severe cases among the three outbreaks and the absence of dengue hemorrhagic shock or mortality are not representative of adult infection in areas of South Vietnam (McBride et al, 2019) or of clinical outcomes in other dengue endemic regions of Asia which report prolonged hospital stay with mortality among severe adult dengue secondary infection (Khalil et al, 2014;Mallhi et al, 2017). Previous models and meta-analyses of dengue severity suggest that the classification of dengue and warning signs in addition to 2009 WHO guidelines can be applied to improve the accuracy for differentiating dengue severity in different dengue-endemic countries and regions of Asia due to the differences in population clinical manifestations and exposure to virulent strains of the virus (Rosenberger et al, 2020). The hospitalized dengue cases in Hanoi between October and December were later in the year than the expected peak cases between July and October in North Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…The age-specific severity of primary and secondary dengue has been documented in southern Vietnam where severe dengue and DHF/DSS were reported more frequently among infants and children than in adults (Thai et al, 2011). Although severe dengue with vascular leakage and DSS is more common among children than adults (Trung et al, 2012;Rosenberger et al, 2020), loss of platelets and bleeding is greater in adults than children who have no dengue complications and do not go on to develop DSS (Trung et al, 2012). The economic burden of Dengue in Vietnam, estimated at 95 million USD for the year 2016 is exacerbated by an ever-increasing dengue infection rate; 38,000 reported in 2019 representing a 3.6% increase compared to 2018 (World Health Organization, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…EDITORIAL severe vascular leakage is an entity distinct from other severe manifestations such as bleeding or organ dysfunction, and may be used as a reliable endpoint for intervention research [11]. While definitions for mild and severe dengue disease were established, a clear definition of 'moderate' disease severity was identified as a need for conducting cross-validated research.…”
Section: E D I T O R I a L C O M M E N T A R Y E D I T O R I A L C O mentioning
confidence: 99%